Persatuan Nasional dalam Perspektif Bung Karno dan Kh Hasyim Asyari - Juwono, Hendro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2022)
The problem raised in this paper is the social setting of two religiousnational figures. One represents religion, and the other represents nationalists. The ideas and movements of the two figures became an in-depth and broad discussion in this study. The research method is qualitative with a type of literature research. The object of study is in the form of a primary document that examines many figures between karno and Kh. Hasyim Asy'ari. Then grouping and analysis is carried out using deductive descriptions. Karno and Kh. Hasyim Asy'ari filled each other and colored each other for Indonesian independence. Both received education from childhood, under the care of their families and religious and nationalist leaders. Both are colored by bright thoughts that became the forerunners of the spirit of national unity for Indonesian society which was given a premodial arrangement. The two of them both carry a union. According to Karno, there is no independence without unity. Meanwhile, according to Kh Hasyim Asy'ari, unity is the main force in the struggle, especially in fighting for Indonesian independence, through a jihad fatwa that ignites the national sense of the Indonesian people, namely Hubbul Wathon Minal Iman.